2016
DOI: 10.1002/pc.23980
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of inorganic–organic polymer microgels for catalytic reduction of 4‐nitroaniline in aqueous medium

Abstract: Poly(N‐isopropylacrylamide‐co‐acrylic acid) [p(NiPA‐co‐AAc)] microgel particles were synthesized by free radical precipitation polymerization in aqueous medium. Silver nanoparticles (Ag NPs) were fabricated inside the microgels by in situ reduction method. UV–visible, Fourier transform infrared (FTIR), and dynamic light scattering techniques were used for characterization of pure microgels. The Ag‐p(NiPA‐co‐AAc) hybrid microgels were characterized by UV–visible, FTIR, X‐ray diffraction, and transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Results showed that value of k app was increased from 0.40 × 10 −2 to 0.78 × 10 −2 s −1 with the increase of catalyst dose from 0.146 to 0.390 mg mL −1 , respectively, as given in Table 1 . Actually, high amount of catalyst provides large surface area for the adsorption of reactants and as a result, the value of k app for CR reduction was increased . Tang and coworkers evaluated the effect of catalyst dose on the value of k app for the reduction of methylene blue (MB) using Ag NPs impregnated poly(N‐isopropylacrylamide‐co‐2‐(dimethylamino) ethyl methacrylate) [p(NIpmam‐EMa)] composite microgels catalyst using NaBH 4 reducing agent .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Results showed that value of k app was increased from 0.40 × 10 −2 to 0.78 × 10 −2 s −1 with the increase of catalyst dose from 0.146 to 0.390 mg mL −1 , respectively, as given in Table 1 . Actually, high amount of catalyst provides large surface area for the adsorption of reactants and as a result, the value of k app for CR reduction was increased . Tang and coworkers evaluated the effect of catalyst dose on the value of k app for the reduction of methylene blue (MB) using Ag NPs impregnated poly(N‐isopropylacrylamide‐co‐2‐(dimethylamino) ethyl methacrylate) [p(NIpmam‐EMa)] composite microgels catalyst using NaBH 4 reducing agent .…”
Section: Resultsmentioning
confidence: 94%
“…Although, different metal nanoparticle (MNp) catalysts have been reported for CR reduction, naked MNps possess high surface energy due to which they coagulate rapidly and lose their catalytic activity . Various stabilizing systems like micelles, dendrimers, and microgels have been reported to prevent the aggregation and coagulation of MNps as well as to prolong their life span. Among them, smart polymer microgels are superior supporting materials due to their responsive behavior, tunable particle size, and easy recoverability by centrifugation and ultrafiltration .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[41] The value of ΔS # was calculated from the intercept of plot of ln(k app /T) vs. 1/T and was found as −196.17 J mol −1 K −1 .The negative value of ΔS # shows that the reduction of 4-NP is entropically unfavorable which can be made favorable by adding catalyst. [40] The value of ΔG # was calculated from the following equation, [7] and it needs an input energy to proceed which is provided by the addition of the catalyst.…”
Section: The Catalytic Activity Of P(aa)-ag Toward the Oxidation Rementioning
confidence: 99%
“…[6] However, the aggregation of these nanoparticles due to their high surface charge and surface to volume ratio, decreases their surface area, [7] which results in a decrease in their catalytic activity. [8] To overcome this problem, silver NPs are usually loaded or dispersed in a solid matrix, such as polymeric matrices e.g.…”
Section: Introductionmentioning
confidence: 99%